Pengaruh Literacy Skills dan Task-Based Instruction terhadap Intelectual Skills Siswa Tingkat Dasar - Mohammad Badru Tamam (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
In a society that is changing, schools cannot provide intellectual costs from items of special knowledge for lifelong use. The shift that must occur in the content of teaching is a change from emphasis mainly on certain knowledge items that may soon become obsolete, into changes with intellectual skills that can be applied to a broad and mostly unexpected list of tasks and situations. This study aims to: 1) Assess Literacy skills and task-based instruction influencing students 'intellectual skills 2) Assessing Literacy skills and task-based instruction influences students' basic level of intellectual skills. This research is a type of survey research, namely research conducted using a questionnaire as a research tool. The purpose of survey research is to provide a detailed description of the background, traits, and characteristics that are typical of the case will be made into a general matter. In this study the object was a fifth grade student at SDN Kauman II with 15 students and SDN Kauman III Ngoro Jombang with 13 students. The method of sampling in this study is that this study uses a census system because all elementary level students are sampled. Data analysis using multiple linear regression with the help of spss v. 20. The results of the discussion can be summarized as follows: 1) Literacy skills and task-based instruction have an effect on students 'intellectual skills 2) Literacy skills and task-based instruction have an effect on elementary students' intellectual skills.